2012
DOI: 10.5402/2012/153081
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Pollution by Toxic Elements around the Small-Scale Mining Area, Boroo, Mongolia

Abstract: The objective of this study is to investigate the contamination levels of toxic elements (TEs) in the vicinity of the small-scale mining Boroo area, Mongolia. Samples of surface soil, ground water and human hair were collected around the gold washing or milling places, grassland and village areas. After appropriate preparation, all samples were analyzed for major and toxic elements (TEs) by Particle-Induced X-ray Emission Spectrometry (PIXE). Soil texture, conductivity (EC), pH, total organic carbon (TC) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…However, the authors pointed out that the waste material may be a source of future contamination. Later, Oyuntsetseg et al 55 found Cu, As and Pb enrichment in soils at the Boroo small-scale mining area that exceeded the standard in As (167 mg/kg) and Cu (109 mg/kg) in the gold washing location. In Zaamar Goldfield, Jarsjö et al 56 found elevated soil contents of As (13 mg/kg), Ni (28 mg/kg), Cu (25 mg/kg) and Cr (69 mg/kg) compared to nonlocal backgrounds; however, no metal(loid) exceeded the current standard.…”
Section: Soil Pollution In Mongolian Mining Areasmentioning
confidence: 99%
“…However, the authors pointed out that the waste material may be a source of future contamination. Later, Oyuntsetseg et al 55 found Cu, As and Pb enrichment in soils at the Boroo small-scale mining area that exceeded the standard in As (167 mg/kg) and Cu (109 mg/kg) in the gold washing location. In Zaamar Goldfield, Jarsjö et al 56 found elevated soil contents of As (13 mg/kg), Ni (28 mg/kg), Cu (25 mg/kg) and Cr (69 mg/kg) compared to nonlocal backgrounds; however, no metal(loid) exceeded the current standard.…”
Section: Soil Pollution In Mongolian Mining Areasmentioning
confidence: 99%
“…However, recent reports indicate that these mining activities are often major sources of heavy metal and arsenic pollution in both river water and sediment (Hofmann et al 2010;Enkhdul et al 2010;Oyuntsetseg et al 2012;Brumbaugh et al 2013;Pfeiffer et al 2014). Mercury is known to have been used extensively in the Boroo River subcatchment by the thousands of illegal small-scale, artisanal miners who have used and released Hg into the environment during the gold amalgamation process (Grayson et al 2004;Steckling et al 2011).…”
Section: Introductionmentioning
confidence: 96%
“…The frequent outbreak of fires at the mining sites have a serious impact on environment and health of people as these fumes contain Sulphur compounds laced with heavy metals like mercury, lead and arsenic, Bolormaa Oyuntsetseg et al, (2012). 2 Also they contain high concentrations of volatile organic compounds like Benzene, toluene and xylene which are known to cause cancer. Dust which is observed at these mining sites is a major source of Particulate Matter (PM)10 pollutants.…”
Section: Introductionmentioning
confidence: 99%